Do Ask, Tell, and Show: Contextual Factors Affecting Sexual Orientation and Gender Identity Disclosure for Sexual and Gender Minority People - Leslie W. Suen; Mitchell R. Lunn; Jae Sevelius; Annesa Flentje; Matthew R. Capriotti; Micah E. Lubensky; Carolyn Hunt; Shannon Weber; Mahri Bahati; Ana Rescate; Zubin Dastur; Juno Obedin‐Maliver (2022)
Purpose: Sexual and gender minority (SGM) people-including members of lesbian, gay, bisexual, transgender, and queer communities-remain underrepresented in health research due to poor collection of sexual orientation and gender identity (SOGI) data. We sought to understand the contextual factors affecting how SGM research participants interact with SOGI questions to enhance participant experience and increase the accuracy and sensitivity of research findings. Methods: We recruited SGM adults for in-person semi-structured focus groups or online cognitive interviews from 2016 to 2018. During focus groups and cognitive interviews, we asked participants to respond to SOGI question sets. We employed template analysis to describe the contextual factors that affected SGM participants' responses to SOGI questions. Results: We had a total of 74 participants, including 55 participants organized into nine focus groups and 19 participants in cognitive interviews. Most self-identified as a sexual minority person (88%), and 51% identified as a gender minority person. Two main themes were: (1) the need to know the relevance (of why SOGI questions are asked) and (2) the importance of environmental and contextual cues (communicating physical safety and freedom from discrimination that influenced SOGI disclosure). Conclusions: Contextualizing the relevance of SOGI data sought could help improve the accuracy and sensitivity of data collection efforts. Environmental cues that communicate acceptance and safety for SGM individuals in research settings may support disclosure. Researchers should consider these contextual factors when designing future studies to improve research experiences for SGM individuals and increase the likelihood of future participation.